Management of Herpes Zoster in Ayurveda Through Jalaukavcharan along with other Ayurvedic Medicines (AYUSHDHARA, 2024)
Herpes zoster, commonly known as shingles, is a viral infection caused by the varicella-zoster virus (VZV), which is the same virus responsible for chickenpox. After a person has had chickenpox, the virus remains dormant in the nervous system. Later in life, usually when the immune system is weakened due to age, stress or other factors, the virus can reactivate and cause shingles. The main symptom of shingles is painful rash that usually appears unilaterally as a band or strip of blisters. Other symptoms may include fever, headache, fatigue and sensitivity to light. Although shingles is contagious, it cannot be transmitted through casual contact. The virus can only be transmitted through direct contact with the fluid from the blisters of an infected person. In Ayurveda Herpes zoster can be correlated with Raktpradoshaj Vikar, Kaksha, Pittaj Kshudra Rog (a Pitta predominant disease.). Clinical Findings: Here we discuss the case of a 55years old female patient came to OPD of NIA Jaipur, with symptoms of unilateral onset of blisters on the left thigh spreading to anteroposterior surface, after three days of onset of blisters, along with burning pain, itching, sleeplessness and difficulty in lying from left side. Diagnosis: According to Ayurveda, the patient was diagnosed with Kaksha, a Pittaj Kshudra Rog. Intervention: Treatment was planned on the basic principles of Pittaj Visarp, Raktmokshan with Jalauka and Ayuvedic medicines for internal use. Outcome: Relief in pain and burning sensation was observed after first sitting of Jalauka and after 28 days of Jalaukavacharan along with Ayurvedic internal medicines gave complete relief from blister formation, pain and normal skin complexion appeared. Conclusion: Application of Jalauka reduces post herpetic neuralgia and recurrence of herpes infection.